Production of reduced graphene oxide-based electrically conductive hydrogel by using modified chitosan - ALEMDAR YAYLA, NESLİHAN (WILEY, 2019)
Herein, a new approach was applied to produce reduced graphene oxide (RGO)-based conductive hydrogel by using modified chitosan (CTS) as a primary constituent. A variety amounts of RGO (from 0 to 15%) were incorporated into the polymeric network generated by photopolymerization of CTS-graft-glycidyl methacrylate (CTS-g-GMA) and poly(ethylene glycol)diacrylate (PEGDA). The structures of hydrogels were confirmed by FT-IR, XRD, and SEM analyses. Water uptake capacity of hydrogels determined gravimetrically. L929 fibroblast cells were used for cytotoxicity test. According to conductivity measurements carried out by four-point probe technique, the highest conductivity (1.716 x 10(-3) S/cm) was obtained when 10% RGO was encapsulated into the polymeric structure. From the results, it could be envisaged that electroconductive hydrogel (ECH) fabricated in this study could have a potential usage for biosensor applications in the future projects. (c) 2019 Wiley Periodicals, Inc.
Keywords: biomaterials; conducting polymers; gels; PERFORMANCE; MEMBRANES; COMPOSITES; CHEMISTRY; EVOLUTION; ACID